(untitled) (Minerva, 2019)
There exist three biographies of St. Radegunda (520-587): two of them written by authors who coexisted with this female saint (one by Venancio Fortunato, who was intimately bound to Radegunda and the Monastery of the Holy Cross; another by Baudonivia, who was a nun at this monastery), and a third one, written in the XIIth Century by Hildeberto de Lavardin. The three of them present individual Prologues, but, whereas the ones by Baudonivia and Hildeberto present the same approach, in accordance with traditional hagiography, the one by Fortunato is quite different. Both Baudovinia and Hildeberto (and also Fortunato in his own prefaces to the lifes of bishops who became saints) insist that they are asked to write the biography by a superior, to whom is dedicated the “Life”. They insist that they are not endowed with sufficient qualities to write a proper work, but they prefer to appear as bad writers than disobedient, while at the same time they trust in the good will of the readers. The prologue by Fortunato, on the other hand, focuses exclusively upon one idea (which will become a cliché): once that woman is no longer persecuted, and can accordingly no longer suffer martyrdom, she can only reach sanctity through the overcoming and the annihilation of her own sex, that is to say, through the assimilation of her sex to the sex of men, which is exemplified with multiple examples of women who, disguised as men, entered male monasteries and remained there until their death.